A modified indirect extraction method for a single-phase shunt active power filter with smaller DC-link capacitor size. (June 2021) - Fallah, Mehdi; Modarresi, Javad; Madadi Kojabadi, Hossein; Chang, Liuchen; Guerrero, Josep M.
Abstract: Indirect extraction method is the most common method to control the single-phase active power filters (APFs) due to its simple structure. The main drawback of this extraction method is its performance dependency on the quality of the DC-link voltage. Selecting the high capacity of the DC-link capacitor leads to the high cost and size of APF, weak dynamic response and low-even-order harmonic components on the DC-link voltage. The low capacity of the DC-link capacitor decreases the cost and size of APF, decreases the sub-harmonics and inter-harmonics of the DC-link voltage, improves the dynamic response, and increases the even-order voltage harmonics. This paper proposes a new extraction method to improve the performance of the conventional indirect extraction method. The proposed method uses a small size of capacitor to achieve the aforementioned advantages. The even-order voltage harmonics are eliminated by the single-frequency-decoupled (SFD) scheme. For implementation of the SFD scheme, the proposed method uses proportional-resonant (PR) controllers, and second order generation integrator-frequency locked loop (SOGI-FLL). The effectiveness of the proposed extraction method is verified by the simulation and experiment.